Coated loperamide hydrochloride fine granule and preparation method thereof

By developing coated loperamide hydrochloride fine granules, the problem of poor drug compliance and slow release rate in pediatric and elderly patients is solved, and a fine granules with a particle size of less than 850μm is achieved to mask the bitter taste and quick release effect, suitable for acute diarrhea treatment.

CN119112827APending Publication Date: 2024-12-13ZHEJIANG LIBERI BIOPHARMACEUTICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324877.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2024-09-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing loperamide hydrochloride preparations have poor drug compliance in pediatric and elderly patients, and the release rate is slow, so they cannot take effect quickly, especially for the treatment of acute diarrhea.

Method used

Developed coating loperamide hydrochloride fine granules with a particle size of less than 850μm, including a powder layer and a coating layer. The coating layer is composed of a coating resin and an anti-adhesive agent. The coating resin contains electron donating groups to mask the bitter taste. And improve binding strength, anti-adhesive agents are used to improve interparticle adhesion and fluidity.

Benefits of technology

It improves the medication compliance and swallowing convenience of loperamide hydrochloride, achieves rapid release and light resistance, and is suitable for the treatment needs of children, the elderly and patients with acute diarrhea.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119112827A_ABST
    Figure CN119112827A_ABST
Patent Text Reader

Abstract

The invention relates to the field of pharmaceutical preparations, in particular to coated loperamide hydrochloride fine granules and a preparation method thereof, and the particle size of the coated loperamide hydrochloride fine granules is smaller than 850 microns. The loperamide hydrochloride tablet comprises a medicine powder layer containing loperamide hydrochloride and a coating layer coated outside the medicine powder layer, the coating layer is composed of coating resin and an anti-sticking agent; and the coating resin contains an electron donating group capable of providing electrons in loperamide hydrochloride for pairing. The coated loperamide hydrochloride fine granule provided by the invention is small in particle size, and can be rapidly swallowed by using water or only needing a small amount of water without chewing, so that patients with poor swallowing functions can effectively and conveniently take medicine. The drug layer is coated with the coating layer, and coating resin in the coating layer is screened, so that the light resistance of the loperamide hydrochloride, the bitter taste of the loperamide hydrochloride and the swallowing convenience of the loperamide hydrochloride are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Chinese patent application No. 202311246467X filed on September 26, 2023, and the entire contents of the above specification are incorporated herein by reference.

[0002] The invention relates to the field of pharmaceutical preparations, and in particular to a coated loperamide hydrochloride fine granule and a preparation method thereof. Background Art

[0003] The molecular formula of loperamide hydrochloride is C 29 H 34 C l2 N2O2, its chemical structure is as follows:

[0004] Loperamide hydrochloride is a white or off-white crystalline powder with an extremely bitter taste. It can be used as an antidiarrheal drug or a long-acting antidiarrheal drug, and is mostly used to treat symptoms such as acute and chronic dysentery. It can be used in patients with ileostomy to reduce the amount and frequency of bowel movements and increase the consistency and hardness of stools. The mechanism of action of loperamide hydrochloride is mainly to inhibit the opioid receptors in the intestinal wall and block the release of acetylcholine and prostaglandins, antagonize the contraction of smooth muscles, reduce intestinal peristalsis and secretion, and prolong the retention time of intestinal contents, thereby playing an antidiarrheal effect.

[0005] Loperamide hydrochloride is clinically used for the symptomatic treatment of non-infectious acute and chronic diarrhea caused by various reasons. Loperamide hydrochloride has been included in the Chinese Pharmacopoeia as an antidiarrheal drug in the form of capsules. Most common loperamide hydrochloride preparations on the market are capsules or tablets. In the field of pediatrics and geriatric medicine, about 50% of people have difficulty swallowing tablets and capsules. The dosage form of loperamide hydrochloride capsules or tablets affects the compliance of drug treatment. In order to overcome the above dosage form deficiencies, a coated API is developed to solve this problem.

[0006] Orally disintegrating granules are a new type of oral solid preparation that has appeared in the domestic and international pharmaceutical markets in recent years. The characteristic is that the drug is placed on the tongue and can be swallowed through the mouth without water or with only a small amount of water, and there is no need to chew, to achieve the therapeutic effect. Coating is common in micro-pellets or tablets larger than 300um, and the technology for coating APIs smaller than 200um is still extremely challenging.

[0007] Loperamide hydrochloride tastes very bitter, and a little exposure of the raw material drug will make people feel nauseous and even vomit. The earliest listed preparation of loperamide hydrochloride is a capsule, and the current listed drugs are still mainly tablets and capsules. Because ordinary tablets and capsules need to be swallowed with water, they are difficult to swallow due to the large volume and the bitter taste of loperamide hydrochloride itself, which is not suitable for infants, critically ill patients and elderly patients. In addition, tablets and capsules must disintegrate in the stomach and can begin to release drugs, which is slow to take effect, and the blood drug concentration needs 30-40min to reach the peak value, which can not quickly reach the effect of antidiarrhea, and this can not play a quick effect for the treatment of acute diarrhea.

[0008] The related patents of loperamide hydrochloride in the prior art are as follows: CN10454673A discloses a loperamide hydrochloride orally disintegrating tablet and a preparation method thereof, wherein the drug powder is bonded and formed by spraying an adhesive by a 3D printer nozzle, but the process is relatively complicated.

[0009] CN104546736A discloses loperamide hydrochloride granules for children and a preparation process thereof. The granules are prepared by a wet method and sucrose is used to mask the bitter taste of the drug. However, the finished granules are sieved through a 16-mesh sieve and have a relatively large particle size.

[0010] CN11121444A discloses an orally disintegrating tablet containing a solid dispersion of loperamide hydrochloride and a preparation method thereof. The orally disintegrating tablet can rapidly disintegrate within 30 seconds and has a good taste. However, the preparation method is relatively complicated and needs to be prepared into a solid dispersion first. The preparation method of the solid dispersion is a spray drying method.

[0011] CN102210661A discloses an oral fast-dissolving film and a preparation method thereof. The oral fast-dissolving film is prepared by using gas electrospinning technology, and the process is relatively complicated. At the same time, the obtained oral fast-dissolving film has the disadvantages of poor uniformity, poor toughness, slow dissolution and dispersion in the mouth, etc.

[0012] In view of the shortcomings of existing preparation technology, it is necessary to develop a new type of coated loperamide hydrochloride oral fine granules that can improve the patient's compliance with medication. In this application, we coat the fine granules of loperamide hydrochloride less than 200um to make oral fine granules, thereby solving the problem of dysphagia for children and the elderly and improving the palatability of patients. Summary of the invention

[0013] The present application aims to overcome the defects of loperamide hydrochloride preparations in the prior art, such as poor palatability for patients, slow release rate in the stomach, and inability to quickly take effect in the treatment of acute diarrhea. Therefore, a coated loperamide hydrochloride fine granule and a preparation method thereof are provided to overcome the above-mentioned shortcomings.

[0014] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions: In a first aspect, the present invention first provides a coated loperamide hydrochloride fine granule, The particle size of the coated loperamide hydrochloride fine granules is less than 850 μm; The invention comprises a drug powder layer containing loperamide hydrochloride and a coating layer coated on the outside of the drug powder layer; The coating layer is composed of a coating resin and an anti-sticking agent; The coating resin contains an electron-donating group capable of providing electrons for loperamide hydrochloride to perform pairing.

[0015] The coated loperamide hydrochloride fine granules in the present application have a smaller particle size range than the capsules, tablets, granules, etc. in the prior art, and the particle size is less than 850 μm. Therefore, during the administration process, it is only necessary to place the medicine on the tongue, without water or only a small amount of water, and without chewing, and it can be quickly swallowed, thereby effectively facilitating the medication of patients, the elderly, and children with poor swallowing function and difficulty in obtaining water.

[0016] At the same time, the coated loperamide hydrochloride fine granules in the present application are coated with a coating layer on the outside of the drug powder layer containing loperamide hydrochloride, so it can isolate the bitter taste of loperamide hydrochloride to a certain extent, thereby improving the compliance of patients when taking the loperamide hydrochloride fine granules.

[0017] However, since loperamide hydrochloride has a very strong bitter taste, even a small amount of extravasation of loperamide hydrochloride will cause the coated loperamide hydrochloride fine granules to have a bitter taste that is difficult to swallow. In view of this technical problem, the applicant found in the experiment that the constituent materials of the coating layer have an important influence on the bitter taste shielding performance of loperamide hydrochloride. Although there are many coating materials in the prior art, not all coating materials are applicable to the coated loperamide hydrochloride fine granules described in the present application.

[0018] The applicant found that the bitter taste of loperamide hydrochloride mainly comes from the nitrogen atom in the dimethylamino group in its molecular structure. Since the nitrogen atom is directly connected to a carbonyl group, the electron-withdrawing property of the nitrogen atom is greatly improved, resulting in an unbearable bitter taste. Therefore, the applicant found in practice that if the coating resin in the coating layer contains an electron-donating group that provides electrons to pair with loperamide hydrochloride, it can greatly improve the taste-masking performance of the coated loperamide hydrochloride and the compliance of taking the drug.

[0019] The coating resin selected for use in the present application contains an electron-donating group, so the electron-donating group in the coating resin can be paired with the nitrogen atom connected to the carbonyl group in the coated loperamide hydrochloride during the coating process, so that the electron cloud stability of the nitrogen atom can be effectively improved, thereby suppressing its bitter taste. In addition, since the coating resin can be combined with loperamide hydrochloride, the present invention can also greatly improve the coverage of loperamide hydrochloride and the bonding strength between loperamide hydrochloride and the coating resin. In addition, loperamide hydrochloride has photosensitivity, and it will deteriorate under light conditions, thereby causing drug failure. The present application sets a coating layer outside loperamide hydrochloride, which can improve its light resistance from the disclosure of physical isolation on the one hand, and on the other hand, due to the combination of loperamide hydrochloride with the coating resin, its own stability has been improved to a certain extent, and the seeds naturally improve their light resistance.

[0020] In addition to the above advantages, the present application also has the following effects: (1) Due to the presence of electron-donating groups in the coating resin, it can also play a good binding role with water, thereby improving the affinity of the loperamide hydrochloride fine granules with water, so that the loperamide hydrochloride fine granules in the present application can be moistened only by the moisture in the oral cavity, further improving the swallowing convenience of the loperamide hydrochloride fine granules; (2) After loperamide hydrochloride is combined with the coating resin, it will not dissociate under near-neutral pH conditions and room temperature conditions, and when entering the stomach, it will quickly dissociate under strongly acidic conditions, thereby achieving rapid release of loperamide hydrochloride.

[0021] Therefore, in summary, the loperamide hydrochloride fine granules in the present application are convenient for patients with poor swallowing function to take due to their small particle size. At the same time, by coating the drug layer of loperamide hydrochloride with a coating layer and screening the coating resin in the coating layer, the light resistance of loperamide hydrochloride, the bitter taste of loperamide hydrochloride itself, and the convenience of swallowing are further improved.

[0022] Preferably, the coated loperamide hydrochloride fine granules have, by mass percentage, a loperamide hydrochloride content of 40%-60%, a coating material content of 35%-55%, and a moisture content of no more than 5%.

[0023] The coated loperamide hydrochloride fine granules in the present application limit the weight ratio of the coating layer to the raw material layer. When the weight ratio of the coating layer is too low, the coating thickness will be too thin or even unable to completely coat the coated loperamide hydrochloride, causing the leakage of loperamide hydrochloride and the decline of light resistance. However, when the weight ratio of the coating layer is too high, the coating layer will be too thick, slowing down the release rate of loperamide hydrochloride and failing to achieve the effect of rapid release.

[0024] Preferably, the large electron-donating group in the coating resin includes any one of a dialkylamine group, a hydroxyl group, a carboxyl group and an alkoxy group.

[0025] The electron donating group selected for use in the present application is any one of dialkyl amido, hydroxyl and alkoxy, and the reason is that these groups all have lone pair electrons, and electrons can be given to the loperamide hydrochloride molecule. From the molecular orbital theory, this electron giving can make the energy of the highest occupied molecular orbital (HOMO) of the loperamide hydrochloride molecule rise, and the electron cloud density increases. After the electron cloud density of loperamide hydrochloride increases, the free radical produced during illumination is just difficult to capture electrons from its molecule, thereby reduces the oxidized possibility of loperamide hydrochloride.

[0026] The nitrogen atom in the dialkylamine group has a lone pair of electrons, and electrons can be donated to the loperamide hydrochloride molecule. From the molecular orbital theory, this electron donation can increase the energy of the highest occupied molecular orbital (HOMO) of the loperamide hydrochloride molecule, and the electron cloud density increases. The adjustment of this electronic structure can enhance the chemical stability of the loperamide hydrochloride molecule as a whole, reduce the tendency of redox reaction with free radicals, and play a role in protecting loperamide hydrochloride from being oxidized.

[0027] In addition, these electron-donating groups can enhance the interaction between the coating resin and loperamide hydrochloride. From a physical and chemical point of view, the interaction between molecules includes van der Waals forces, hydrogen bonds, etc. Dialkylamine groups, hydroxyl groups, carboxyl groups, and alkoxy groups can form hydrogen bonds or enhance van der Waals forces to make the coating resin better attached to the surface of the loperamide hydrochloride drug layer, thereby improving the integrity and stability of the coating layer and better protecting the drug.

[0028] In addition, the presence of these electron-donating groups may affect the release process of the drug in vivo. They may interact with the biological environment in the body (such as certain components in body fluids) to regulate the dissolution rate or permeability of the coating layer. For example, hydroxyl groups may form hydrogen bonds with water molecules. Under appropriate conditions, this interaction may affect the dissolution rate of the coating layer, thereby controlling the release rate of loperamide hydrochloride to achieve an ideal drug efficacy mode.

[0029] Preferably, the coating resin is a combination of one or more of hydroxypropyl methylcellulose, hydroxypropyl cellulose, acrylic resin, polyvinyl pyrrolidine, hydroxypropyl methylcellulose phthalate, and styrene maleic acid copolymer.

[0030] Preferably, the anti-sticking agent is any one of talc and glyceryl mono- and distearate; The mesh number of the anti-sticking agent is greater than or equal to 1000 meshes.

[0031] In this application, talcum powder has good lubricity and hydrophobicity. In the coating layer of fine granules, talcum powder can form a thin isolation layer on the surface of the particles, reducing the direct contact area between the particles, thereby reducing the adhesion between the particles. This helps to prevent the fine granules from sticking together during storage and transportation, and ensures the fluidity and operability of the drug. And mono- and di-stearate glyceryl is a surfactant with dual properties of lipophilicity and hydrophilicity. In the coating layer, it can reduce the surface energy of the particle surface, making it difficult for the particles to stick to each other. At the same time, it can also improve the uniformity and smoothness of the coating layer and improve the appearance quality of the drug.

[0032] In addition, the inventors of the present application have found that the mesh number of the anti-adherent agent has an important influence on the performance of the overall fine granules. It has been found in practice that when the mesh number of the anti-adherent agent is greater than or equal to 1000 meshes, the anti-adherent agent particles are very fine. During the coating process, these fine particles can be more evenly dispersed in the coating layer and fully mixed with the coating resin. This makes the texture of the coating layer more uniform, avoiding the problem of local adhesion or unstable performance caused by uneven distribution of the anti-adherent agent. At the same time, good dispersibility also helps to improve the uniformity of coverage of the coating layer on the raw material layer, thereby better playing a protective role.

[0033] At the same time, high-mesh anti-adhesives have a larger specific surface area. This means that at the same mass, they can contact more particle surfaces and provide better anti-adhesive properties. Fine particles can be more tightly filled in the gaps between particles, forming a more effective isolation layer, further reducing the adhesion between fine particles and ensuring that the drug maintains good fluidity during storage and transportation.

[0034] In addition, due to the small particles of high-mesh anti-adherent agents, they can make the surface of the coating layer smoother and more delicate. This not only improves the appearance quality of the drug, but also reduces the wear and tear of the coating layer during use. The smooth surface also helps to reduce the friction between the drug and the external environment, reducing the possibility of the drug being affected by external factors.

[0035] Preferably, the powder layer further includes a coating resin less than 1% by weight of loperamide hydrochloride.

[0036] The drug powder layer in the present application contains a certain amount of coating resin because it can effectively improve the binding force, stability and taste-masking performance of loperamide hydrochloride inside the drug powder layer.

[0037] In a second aspect, the present invention also provides a method for preparing the coated loperamide hydrochloride fine granules, which comprises the following steps: (S.1) crushing and sieving the loperamide hydrochloride raw material to obtain raw material powder; (S.2) dissolving the anti-adherent agent and the coating resin in a solvent and homogenizing to obtain a coating premix; (S.3) adding loperamide hydrochloride bulk drug powder into a fluidized bed, and then spraying the coating premix liquid onto the bottom of the fluidized bed, controlling the speed of the sprayed liquid and the volatilized liquid to be equal, thereby coating a coating layer on the surface of the loperamide hydrochloride bulk drug; (S.4) Drying and sieving the coated material to obtain the coated loperamide hydrochloride fine granules.

[0038] In the present application step (S.3), coating operation is carried out in a fluidized bed, and loperamide hydrochloride bulk drug powder is in a fluidized state, and each particle can be fully exposed to the spray of the coating premix. At the same time, the liquid sprayed into is controlled to be equivalent to the liquid speed of volatilization, so that the coating material can be uniformly deposited on the bulk drug surface, forming a coating layer with uniform thickness, effectively improving the stability and controllability of the drug. In addition, the bulk drug powder surface temperature after preheating is relatively uniform, which is conducive to the attachment and drying of the coating material. The bonding force between the coating layer formed under such conditions and the bulk drug is stronger, and it is not easy to cause the coating layer to fall off or break, thereby ensuring the coating quality.

[0039] In addition, the inventors of the present application also found during the test that the direction of the spray coating premix in the fluidized bed has an important influence on the final fine granule formation. The test results show that when the fluidized bed is sprayed with the spray coating premix by bottom spraying, the coating effect of loperamide hydrochloride raw material is the best. When the top spray or side spray is used, the coating effect of the display will be significantly reduced.

[0040] Preferably, the mass percentage concentration of the coating premix in step (S.2) is 3%-10%.

[0041] The inventor of the present application has found that the particle size of loperamide hydrochloride raw material powder is finer and its specific gravity is lighter, so if a coating premix with a larger concentration is used for coating, it is difficult to be evenly coated on the surface of loperamide hydrochloride raw material powder. In the present application, after the mass percentage concentration of the coating premix is ​​3%-10%, the fluidity and viscosity of the coating premix are more moderate. In the coating process, it can be sprayed on the surface of loperamide hydrochloride raw material powder more evenly to form a coating layer with uniform thickness and stable quality. However, if the mass percentage concentration of the coating premix is ​​too low, it may be difficult to achieve the speed of the liquid sprayed in and the volatile liquid equal in the coating process, thereby causing the problem of uneven coating layer, which ultimately leads to the inability to fully play the role of protecting the raw material medicine, covering up the odor and preventing oxidation.

[0042] In addition, the drying time of the coating premix with a solid content of 3%-10% after spraying is relatively reasonable. It will not take too long to dry due to too high a moisture content, affecting production efficiency, nor will it dry too fast due to too low a moisture content, which may cause problems such as cracking of the coating layer. In this way, production efficiency can be improved and production costs can be reduced while ensuring coating quality.

[0043] Finally, the thickness and properties of the coating layer will affect the release rate of the drug in the body, and the choice of solid content can indirectly adjust parameters such as the thickness and porosity of the coating layer. A mass percentage concentration of 3%-10% can make the coating layer have appropriate permeability, thereby achieving a sustained or controlled release effect of the drug and improving the efficacy and safety of the drug.

[0044] Preferably, in step (S.3), the fluidized bed is set with an inlet air temperature of 30°C to 60°C and an inlet air volume of 15-25m 3 / h, backflush pressure 0.2-0.5mpa, atomization pressure 0.2-0.5bar.

[0045] Preferably, the step (S.3) further comprises the step of wetting the loperamide hydrochloride bulk drug powder with a coating premix solution before adding the loperamide hydrochloride bulk drug powder to the fluidized bed, wherein the mass ratio of the loperamide hydrochloride bulk drug powder to the coating premix solution is 100:0.5-2.

[0046] Pre-wetting the loperamide hydrochloride bulk drug powder in the present application during the coating process can make the powder surface have a certain degree of contact with the coating material before entering the fluidized bed for coating. When the powder enters the fluidized bed, this pre-contact can promote the uniform distribution of the coating premix on the powder surface, thereby improving the uniformity of the coating. If there is no pre-wetting, the powder surface may have uneven properties, resulting in uneven adhesion of the coating material during the coating process.

[0047] At the same time, the wetting step allows the API powder to form a preliminary bond with the coating premix. This bond can be further strengthened during the subsequent fluidized bed coating process, thereby increasing the bonding strength between the coating layer and the API powder. This helps ensure that the coating layer is not easy to fall off during storage, transportation and use, ensuring the stability and effectiveness of the drug.

[0048] In addition, the appropriate mass ratio ensures that the powder surface can be fully wetted without causing powder agglomeration or affecting fluidization due to excessive coating premix. Within the mass ratio range of 100:0.5-2, a good foundation can be laid for the subsequent coating process without affecting the fluidity of the powder.

[0049] Therefore, the present invention has the following beneficial effects: (1) The coated loperamide hydrochloride fine granules in the present application have a small particle size and can be quickly swallowed with water or only a small amount of water, without chewing, thereby effectively facilitating medication for patients with poor swallowing function and difficulty in obtaining water, the elderly, and children; (2) The drug layer of loperamide hydrochloride is coated with a coating layer on the outside, and by screening the coating resin in the coating layer, the light resistance of loperamide hydrochloride, the bitter taste of loperamide hydrochloride itself, and the ease of swallowing are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 Original dissolution curve of loperamide hydrochloride capsules.

[0051] Figure 2 Dissolution curve of loperamide hydrochloride self-developed fine granules.

[0052] Figure 3 Bitter emoji. DETAILED DESCRIPTION

[0053] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0054] Example 1 1. Loperamide hydrochloride formula Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula 3. Loperamide Hydrochloride Granule Coating Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 100-mesh sieve.

[0055] Weigh the weight of hydroxypropyl methylcellulose in the table and add it to water, stirring for 30 minutes until it is uniform.

[0056] Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0057] The fluidized bed was set to have an inlet air temperature of 55°C and an inlet air volume of 15m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.2bar. Preheat the material to 40-42℃.

[0058] After the material temperature reaches the target temperature, turn on the peristaltic pump and coat at a rate of 60 ml / h; after coating is completed, turn off the peristaltic pump.

[0059] After continuing to dry at a temperature of 50° C. and the original air inlet speed for 45 minutes, coated loperamide hydrochloride fine particles were obtained, wherein the loperamide hydrochloride content was 58.8% by mass, the coating material content was 39.2% by mass, and the moisture content was less than 2%.

[0060] Example 2 1. Loperamide hydrochloride formula: Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula Material Name Feeding amount / g Hydroxypropyl methylcellulose 112 Purified water 950 1250 mesh talc 10 3. Loperamide Hydrochloride Granule Coating 1. Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 120-mesh sieve.

[0061] 2. Weigh the hydroxypropyl methylcellulose in the table and add it into water, stirring for 30 minutes until it is uniform.

[0062] 3. Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0063] 4. Set the fluidized bed air inlet temperature to 50°C and air volume to 20m 3 / h, backflush pressure 0.2mpa, atomization pressure 0.2bar. Preheat the material to 38-42℃.

[0064] 5. After the material temperature reaches the target temperature, start the peristaltic pump and coat at a rate of 60 ml / h; After coating is complete, turn off the peristaltic pump.

[0065] 6. Continue drying at 50° C. and the original air inlet speed for 45 minutes to obtain coated loperamide hydrochloride fine particles, wherein the loperamide hydrochloride content is 53.9% by mass, the coating material content is 44.1% by mass, and the moisture content is less than 2.0%.

[0066] Embodiment 3: 1. Loperamide hydrochloride formula: Material Name Feeding amount / g Loperamide Hydrochloride 50 2. Coating liquid formula Material Name Feeding amount / g Hydroxypropyl methylcellulose 50 Purified water 950 1250 mesh talc 10 3. Loperamide Hydrochloride Granule Coating 1. Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 120-mesh sieve.

[0067] 2. Weigh the weight of hydroxypropyl methylcellulose in the table and add it to water. Stir for 30 minutes until it is uniform.

[0068] 3. Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0069] 4. Set the fluidized bed to an air inlet temperature of 58°C and an air volume of 12m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.2bar. Preheat the material to 40-45℃.

[0070] 5. After the material temperature reaches the target temperature, start the peristaltic pump and coat at a rate of 58 ml / h; After coating is complete, turn off the peristaltic pump.

[0071] After drying at a temperature of 6.50°C and the original air inlet speed for 45 minutes, coated loperamide hydrochloride fine particles were obtained, wherein the loperamide hydrochloride content was 43.7% by mass, the coating material content was 53.8% by mass, and the moisture content was less than 2.0%.

[0072] Example 4: Preparation of coated loperamide hydrochloride fine granules 1. Loperamide hydrochloride: Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula Material Name Feeding amount / g Polyacrylic acid resin 90 Purified water 285 1250 mesh talc 10 3. Loperamide Hydrochloride Granule Coating 1. Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 120-mesh sieve.

[0073] 2. Weigh the weight of hydroxypropyl methylcellulose in the table, add it to water, add talcum powder, and stir for 30 minutes until it is uniform.

[0074] 3. Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0075] 4. Set the fluidized bed inlet air temperature to 56°C and the inlet air volume to 23m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.2bar. Preheat the material to 40-45℃.

[0076] 5. After the material temperature reaches the target temperature, start the peristaltic pump and coat at a rate of 60 ml / h; After coating is complete, turn off the peristaltic pump.

[0077] After drying at a temperature of 6.50°C and the original air inlet speed for 45 minutes, coated loperamide hydrochloride fine particles were obtained, wherein the loperamide hydrochloride content was 59.5% by mass, the coating material content was 39.7% and the moisture content was 0.8%.

[0078] Example 5 1. Loperamide hydrochloride: Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula Material Name Feeding amount / g Polyacrylic acid resin 92 Purified water 285 1250 mesh talc 30 3. Loperamide Hydrochloride Granule Coating 1. Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 100-mesh sieve.

[0079] 2. Weigh the weight of hydroxypropyl methylcellulose in the table, add it to water, add talcum powder, and stir for 30 minutes until it is uniform.

[0080] 3. Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0081] 4. Set the fluidized bed inlet air temperature to 55°C and the inlet air volume to 18m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.2bar. Preheat the material to 40-45℃.

[0082] 5. After the material temperature reaches the target temperature, turn on the peristaltic pump and coat at a rate of 58 ml / h; after coating is completed, turn off the peristaltic pump.

[0083] After drying for 45 minutes at a temperature of 6.50°C and the original air inlet speed, coated loperamide hydrochloride fine particles were obtained, wherein the loperamide hydrochloride content by mass percentage was 53.9%, the coating material content was 44.1%, and the moisture content was less than 2.0%.

[0084] Embodiment 6: 1. Loperamide hydrochloride: Material Name Feeding amount / g Loperamide Hydrochloride 130 2. Coating liquid formula Material Name Feeding amount / g Hydroxypropyl methylcellulose 50 Polyethylene glycol 35 Stevioside 2 1250 mesh talc 1 Purified water 857 3. Loperamide Hydrochloride Granule Coating 1. Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 120-mesh sieve.

[0085] 2. Weigh the weight of hydroxypropyl methylcellulose in the table and add it to water. Stir for 40 minutes until it is uniform.

[0086] 3. Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0087] 4. Set the fluidized bed to an air inlet temperature of 50°C and an air volume of 150m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.2bar. Preheat the material to 40-42℃.

[0088] 5. After the material temperature reaches the target temperature, turn on the peristaltic pump and coat at a rate of 60 ml / h; 6. After coating is completed, turn off the peristaltic pump.

[0089] After drying at a temperature of 7.50°C and the original air inlet speed for 45 minutes, coated loperamide hydrochloride fine particles were obtained, wherein the loperamide hydrochloride content by mass percentage was 58.4%, the coating material content was 39.6%, and the moisture content was less than 2.0%.

[0090] Example 7 1. Loperamide Hydrochloride Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula Material Name Feeding amount / g Hydroxypropyl methylcellulose 50 Polyethylene glycol 47 Aspartame 2 1250 mesh talc 1 Purified water 880 2. Loperamide hydrochloride fine granule coating 1. Weigh the loperamide hydrochloride raw material in the table, grind it and pass it through a 100-mesh sieve.

[0091] 2. Weigh the weight of hydroxypropyl methylcellulose in the table and add it to water. Stir for 40 minutes until it is uniform.

[0092] 3. Put the sieved API into the fluidized bed, adopt the bottom spray coating mode, and start the fluidized bed.

[0093] 4. Set the fluidized bed to an air inlet temperature of 55°C and an air volume of 15m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.2bar. Preheat the material to 40-45℃.

[0094] 5. After the material temperature reaches the target temperature, turn on the peristaltic pump and coat at a rate of 60 ml / h; after coating is completed, turn off the peristaltic pump.

[0095] 6. Continue drying at 50° C. and the original air inlet speed for 45 minutes to obtain coated loperamide hydrochloride fine particles, wherein the loperamide hydrochloride content is 58.8% by mass, the coating material content is 39.2% by mass, and the moisture content is less than 2.0%.

[0096] Comparative Example 1 The process parameters of Comparative Example 1 are basically the same as those of Example 1, except that the hydroxypropyl methylcellulose is replaced by an equal amount of ethyl cellulose.

[0097] Comparative Example 2 The process parameters of Comparative Example 2 are basically the same as those of Example 1, except that the hydroxypropyl methylcellulose is replaced by an equal amount of cellulose acetate.

[0098] Comparative Example 3 The process parameters of Comparative Example 3 are basically the same as those of Example 1, except that the 1250-mesh talc powder is replaced with an equal amount of 800-mesh talc powder.

[0099] Comparative Example 4 The process parameters of Comparative Example 4 are basically the same as those of Example 1, except that the bottom spray coating liquid of the fluidized bed is replaced by the top spray coating liquid. The fluidized bed parameters are as follows: Air volume: 15m 3 / h, inlet air temperature: 50℃, atomization pressure: 0.1 MPa, back-blowing pressure: 0.6 MPa.

[0100] Comparative Example 5 The process parameters of Comparative Example 5 are basically the same as those of Example 1, except that the bottom spray coating liquid of the fluidized bed is replaced by the side spray coating liquid. The fluidized bed parameters are as follows: Inlet air volume: 15m 3 / h, inlet air temperature: 50℃, atomization pressure: 0.1 MPa, back-blowing pressure: 0.6 MPa.

[0101] Comparative Example 6 The process parameters of Comparative Example 6 are basically the same as those of Example 1, except that the fluidized bed parameters are changed as follows: inlet air temperature 70°C, inlet air volume 10m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.1bar. Preheat the material to 40-42℃.

[0102] Comparative Example 7 The process parameters of Comparative Example 7 are basically the same as those of Example 1, except that the fluidized bed parameters are changed as follows: inlet air temperature 25°C, inlet air volume 20m 3 / h, backflush pressure 0.3mpa, atomization pressure 0.1bar. Preheat the material to 25℃.

[0103] Comparative Example 8 The process parameters of Comparative Example 8 are basically the same as those of Example 1, except that the raw material formula is adjusted.

[0104] 1. Loperamide hydrochloride formula: Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula Material Name Feeding amount / g Hydroxypropyl methylcellulose 300 Purified water 950 1250 mesh talc 30

[0105] Comparative Example 9 The process parameters of Comparative Example 8 are basically the same as those of Example 1, except that the raw material formula is adjusted.

[0106] 1. Loperamide hydrochloride formula: Material Name Feeding amount / g Loperamide Hydrochloride 150 2. Coating liquid formula Material Name Feeding amount / g Hydroxypropyl methylcellulose 50 Purified water 950 1250 mesh talc 15 .

[0107] The coated loperamide hydrochloride fine granules prepared in Examples 1-7 and Comparative Examples 1-9 were tested, and the test methods and results are as follows: 1. Bitterness masking performance test method: The taste of the homemade coated loperamide hydrochloride granules was compared with the loperamide hydrochloride (capsule) reference preparation, with a score of 0-10. The lighter the bitterness, the lower the score.

[0108] Method: Self-developed samples were directly sampled from coated loperamide hydrochloride granules for oral tasting; reference preparation capsules were opened and the powder was taken out for oral tasting. Figure 3 The bitter taste expression diagram shown in the figure is scored and counted, and the taste is evaluated. Among them: When the score is 0, it is evaluated as not bitter and does not affect the taste; When the score is 1-3, it is evaluated as a little bitter, but does not affect the taste; A score of 4-6 is considered slightly bitter, which slightly affects the taste; When the score is 7-10, it is considered extremely bitter and seriously affects the taste.

[0109] 2. Drug release test method under different pH environments: The same batch of loperamide hydrochloride fine granules were subjected to drug dissolution and release experiments at pH 4.7 and pH 7.

[0110] Dissolution: Determine according to the dissolution and release method (General Rule 0931 Method 1).

[0111] Dissolution conditions: Use 500 ml of pH 4.7 acetate buffer (take 200 ml of 1 mol / L acetic acid solution, add 600 ml of water, mix well, adjust the pH value to 4.7±0.05 with 1 mol / L sodium hydroxide solution, and dilute to 1000 ml with water) as the dissolution medium, the rotation speed is 100 revolutions per minute, operate according to the method, and sample after 30 minutes.

[0112] Test solution: Take an appropriate amount of the dissolution solution, filter it, and take the filtrate.

[0113] Reference solution: Take about 20 mg of loperamide hydrochloride reference substance, accurately weigh it, place it in a 100ml volumetric flask, add an appropriate amount of methanol to dissolve it, and dilute it with dissolution medium until it is well mixed; accurately measure 2 ml, place it in a 100ml volumetric flask, dilute it to the scale with dissolution medium, and shake it well.

[0114] 3. Lightfastness test: 1. Place the finished coated products in the following environments: 2. Use the content detection method for loperamide hydrochloride granules in the "Chinese Pharmacopoeia 2020 Edition": the content is determined according to high performance liquid chromatography (General Rule 0512).

[0115] Test solution: Take 5 portions of the product and place it in a stoppered conical flask. Accurately add 100 ml of methanol. Shake for 30 minutes. Centrifuge for 3 minutes at 3500 rpm and take the supernatant.

[0116] Reference solution: Take an appropriate amount of loperamide hydrochloride reference substance, weigh accurately, dissolve in methanol and quantitatively dilute to make a solution containing 0.1 mg per 1 ml.

[0117] Chromatographic conditions: octadecylsilane bonded silica gel was used as filler; 0.01 mol / L tetrabutylammonium hydrogen sulfate solution-acetonitrile-methanol (63:26:11) was used as mobile phase; detection wavelength was 220 nm; injection volume was 20 μl.

[0118] System suitability requirements: The number of theoretical plates calculated based on the loperamide peak is not less than 3000.

[0119] Determination method: Accurately measure the test solution and reference solution, inject them into the liquid chromatograph respectively, record the chromatogram, and calculate by peak area according to the external standard method.

[0120] Test the content before and after placement: Test the content 1 hour, 5 hours, 12 hours, and 24 hours after placement, and make a final comparison.

[0121] Drug dissolution rate test: Test method: According to the first method of the Chinese Pharmacopoeia dissolution and release test method - basket method, 500ml of pH 4.7 acetate buffer was selected for dissolution test at 100rpm / min, and the sampling points were set at 5, 10, 20, 30, 45, and 60min. Two different batches of the original loperamide hydrochloride capsules (reference reagent-1 and reference reagent-2) were selected for dissolution test with n=6. The experimental results are shown in Figure 1 .Depend on Figure 1 The results showed that there were batch differences between different batches of loperamide hydrochloride capsules. The dissolution rate reached 80% in 30 minutes, but the endpoint dissolution rate was poor, averaging about 90%. The theoretical dissolution rate could reach 100%.

[0122] The basket method was still used to test the dissolution of three batches of loperamide hydrochloride fine granules with different self-developed coatings under the same parameters. The results are shown in Figure 2 . Figure 2It can be clearly seen that compared with the original loperamide hydrochloride capsule (reference reagent-1), the coated loperamide hydrochloride fine granules can achieve rapid release, and can reach the pharmacopoeia's dissolution requirements in 10 minutes, with a fast onset of action, and there is no difficulty in swallowing for the coated loperamide hydrochloride fine granules. In addition, the 60-minute endpoint dissolution can stably reach 95%, greatly improving the drug utilization rate, and the batch-to-batch difference is significantly reduced.

[0123] The bitter taste masking performance and drug release test results under different pH environments are shown in the following table: The light resistance test results are shown in the following table: It can be seen from the data in the above table that the loperamide hydrochloride fine granules prepared in Examples 1-7 of the present application have good bitterness masking performance and a rapid release effect under simulated gastric acid conditions, and also have good light resistance.

[0124] By comparing Example 1 with Comparative Examples 1-2, we can see that the selection of coating resin in the coating material has an important influence on its storage performance, bitterness masking performance and drug release test under different pH environments. When the coating resin lacks electron-donating groups that can provide electrons for pairing in loperamide hydrochloride, its performance will be greatly reduced.

[0125] By comparing Example 1 with Comparative Example 3, we found that the particle size of the anti-adhesive agent (talcum powder) also has an important influence on the loperamide hydrochloride fine granules. When the particle size of the anti-adhesive agent is too large, its performance will decline to a certain extent.

[0126] By comparing Example 1 with Comparative Examples 4 and 5, we found that after changing the spraying method of the coating liquid in the fluidized bed, it was found that there were problems of uneven coating and decreased taste masking performance.

[0127] By comparing Example 1 with Comparative Examples 6 and 7, we found that after adjusting the parameters of the fluidized bed, it was not possible to achieve the purpose of controlling the speed of the sprayed liquid and the volatilized liquid to be equal during the coating process, resulting in uneven coating and decreased taste masking performance.

[0128] By comparing Example 1 with Comparative Examples 8 and 9, we found that when the thickness of the coating layer in the coated loperamide hydrochloride fine granules is low, it will have adverse consequences on the antioxidant performance, taste masking performance and drug release performance of the loperamide hydrochloride fine granules. When the thickness of the coating layer is too high, the release rate of the drug after entering the body will be significantly reduced, which is not conducive to the rapid onset of the drug.

[0129] Therefore, in summary, compared with other dosage forms, the present invention has great advantages in terms of process. Compared with the products obtained by the traditional tableting process, various small problems are often encountered during the tableting process, such as loose particles, improper dryness and wetness, or loose tablets, cracks, sticking, surface spots, etc. due to excessive humidity in the air, or abnormal tablet presses such as heavy heads and die ring wear, resulting in a lot of time and cost invested in process optimization, but still unable to perfectly solve a series of problems including excessive impurities and poor stability.

[0130] Compared with capsules, the present invention not only combines many advantages of capsules, but also overcomes many inevitable defects of capsules. The capsule drug particles are relatively large, the manufacturing process is relatively simple, the impurities are more, and the side reactions are relatively more. The present invention is granulated in one step, the impurities are more controllable than capsules, and the present invention does not have the problem of excessively large particles. In addition, the capsule shell is easily softened by water, and humid weather is not conducive to storage. The present invention can be stored in a storage method different from the capsule shell. The present invention has the advantages of taste masking and easy swallowing like capsules, and the present invention not only has high bioavailability, but also can be prepared like capsules, without considering pressure and adhesives during preparation, and has fast effect and good absorption. The product of the present invention has greater advantages in sub-packaging, such as light-sensitive drugs and drugs that are unstable when exposed to moisture and heat, which can be loaded into opaque aluminum-plastic packaging, or can be changed to bottle packaging according to the characteristics of the drug, to protect the drug from moisture and oxygen in the air, and light, thereby improving its stability. The greater advantage of the present invention is that the formulation range is wide and more diverse options are available; the present invention can also delay the release of drugs and position the release of drugs. For example, the drug can be made into granules first, and then coated with coating materials with different release rates and mixed evenly in the required proportions. If the drug needs to be effective in the intestine, an enteric coating film can be applied.

[0131] In addition, in each process link of conventional tableting and granulation, energy consumption is increased accordingly; however, the process flow of the present invention is simple, and only one step of granulation is required, which greatly saves instrument costs, site costs and labor costs; and the optimization of the process reduces the required energy consumption accordingly, saving corresponding costs.

[0132] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but this will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A coated loperamide hydrochloride fine granule, characterized in that: The particle size of the coated loperamide hydrochloride fine granules is less than 850 μm; The invention comprises a drug powder layer containing loperamide hydrochloride and a coating layer coated on the outside of the drug powder layer; The coating layer is composed of a coating resin and an anti-sticking agent; The coating resin contains an electron-donating group capable of providing electrons for loperamide hydrochloride to perform pairing.

2. The coated loperamide hydrochloride fine granules according to claim 1, characterized in that: The coated loperamide hydrochloride fine granules have a loperamide hydrochloride content of 40%-60% and a coating material content of 35%-55% by mass, and the moisture content is not higher than 5%.

3. The coated loperamide hydrochloride fine granules according to claim 1, characterized in that: The large electron-donating group in the coating resin includes any one of a dialkylamine group, a hydroxyl group, a carboxyl group and an alkoxy group.

4. A coated loperamide hydrochloride fine granules according to claim 1 or 3, characterized in that: The coating resin is a combination of one or more of hydroxypropyl methylcellulose, hydroxypropyl cellulose, acrylic resin, polyvinyl pyrrolidine, hydroxypropyl methylcellulose phthalate, and styrene maleic acid copolymer.

5. The coated loperamide hydrochloride fine granules according to claim 1, characterized in that: The anti-sticking agent is any one of talc and glyceryl mono- and distearate; The mesh number of the anti-sticking agent is greater than or equal to 1000 meshes.

6. The coated loperamide hydrochloride fine granules according to claim 1, characterized in that: The medicine powder layer also includes a coating resin less than 1% by weight of loperamide hydrochloride.

7. A method for preparing the coated loperamide hydrochloride fine granules as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (S.1) crushing and sieving the loperamide hydrochloride raw material to obtain raw material powder; (S.2) dissolving the anti-adherent agent and the coating resin in a solvent and homogenizing to obtain a coating premix; (S.3) adding loperamide hydrochloride bulk drug powder into a fluidized bed, and then spraying the coating premix liquid onto the bottom of the fluidized bed, controlling the speed of the sprayed liquid and the volatilized liquid to be equal, thereby coating a coating layer on the surface of the loperamide hydrochloride bulk drug; (S.4) Drying and sieving the coated material to obtain the coated loperamide hydrochloride fine granules.

8. The method according to claim 7, characterized in that The mass percentage concentration of the coating premix in the step (S.2) is 3%-10%.

9. The method according to claim 7, characterized in that: In step (S.3), the fluidized bed is set with an inlet air temperature of 30°C to 60°C and an inlet air volume of 15-25m 3 / h, backflush pressure 0.2-0.5mpa, atomization pressure 0.2-0.5bar.

10. The method according to claim 7 or 9, characterized in that: The step (S.3) further includes a step of wetting the loperamide hydrochloride bulk drug powder with a coating premix solution before adding the loperamide hydrochloride bulk drug powder to the fluidized bed, wherein the mass ratio of the loperamide hydrochloride bulk drug powder to the coating premix solution is 100:0.5-2.